Employee organizational citizenship behavior : examining the role of transformational leadership and organizational innovation climate - Künzel, Pauline (2024)
While the role of transformational leadership on employees9 organizational citizenship behavior (OCB) is well established, research is in its infancy concerning the role of organizational innovation climate. This research investigated the influence of transformational leadership and organizational innovation climate on OCB. The study hypothesized that transformational leadership directly fosters OCB and that an organizational innovation climate not only promotes OCB but also strengthens the effect of transformational leadership on OCB. Utilizing a cross-sectional survey design with 177 participants from various industries predominantly within Europe, the research employs statistical analyses to test these hypotheses. The findings support the propositions that both transformational leadership and organizational innovation climate have significant, positive relationships with OCB, independently enhancing voluntary employee behaviors that benefit the organization. Contrary to expectations, the study does not support the hypothesis that organizational innovative climate moderates the relationship between transformational leadership and OCB, indicating that each factor individually contributes to fostering OCB. The research underscores the importance of cultivating transformational leadership and an innovative climate as distinct yet complementary strategies to enhance organizational performance through OCB. The study provides new insights and practical implications, while also laying the groundwork for further research on the topic and exploring the interplay between leadership, organizational climate, and employee behavior.